«Нереальный» сектор экономики (Библиосфера)
Culture as an economy sector and some estimation methods of its contribution in social and economic territory development (share in GNP, integrated macroeconomic indicators) are considered. The policy and strategic priorities of culture financing by the state are analyzed.